2017
DOI: 10.1093/jscr/rjx034
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis with acute obstructive suppurative pancreatic ductitis: a rare case report

Abstract: Acute obstructive suppurative pancreatic ductitis (AOSPD) is a rare complication of chronic pancreatitis that has been described in only seven previous case reports since 1995. We report a case of a 33-year-old female a known case of chronic pancreatitis with computed tomography suggestive of dilated main pancreatic duct with multiple calcifications. On exploration, pancreatic duct aspiration revealed frank pus. Pus was drained after opening the pancreatic duct and longitudinal pancreaticojejunostomy was done.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Additionally, with CP, the pancreas may be more susceptible to infection owing to impairment of antibacterial agents compared with normal pancreatic secretions. 3 These factors combine to encourage bacterial growth and proliferation, resulting in acute suppuration of the MPD. 1 Furthermore, in our case, pathology showed that there was granulation and inflammation in the tissues surrounding the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with CP, the pancreas may be more susceptible to infection owing to impairment of antibacterial agents compared with normal pancreatic secretions. 3 These factors combine to encourage bacterial growth and proliferation, resulting in acute suppuration of the MPD. 1 Furthermore, in our case, pathology showed that there was granulation and inflammation in the tissues surrounding the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
“…AOSPD presentation overlaps with cholangitis and this mimicry makes misdiagnosis or non-recognition as a separate clinical entity difficult. AOSPD presentation varies from acute to chronic, the most common symptom being abdominal pain [1][2][3][4][5][8][9][10][11][12] . Less commonly, it may also present as sepsis or septic shock [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…The distinguishing feature is a lack of pseudocyst, abscess, or necrosis formation. Literature remains sparse in the domain of AOSPD, with a recent literature search only mentioning this entity in over 29 cases to date [1][2][3][4][5][6][7][8][9][10][11][12] . Pancreatic malignancy is also known to promote AOSPD by obstructing pancreaticobiliary secretion outflow ensuing in subsequent infection 2,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature were described 14 studies (64 patients) concerning AOSPD, occurred on the background of chronic pancreatitis (Gedam, 2017;Wali, 2015) or as a complication of pancreatic cancer (Iwatsuka, 2018;Sheikh et al, 2020;Shimizuguchi et al, 2020). Gedam, Sadriwala & Bansod (2017) reported about the case of 33-yearold female with chronic pancreatitis, which on ultrasonography was hyper-echoic and atrophic pancreas with main pancreatic duct dilated up to 1…”
Section: Acute Obstructive Suppurative Pancreatic Ductitis (Aospd)mentioning
confidence: 99%
“…Pancreatic abscesses (PA) are attributed to nonspecific surgical abdominal infections, the main cause is purulent-destructive and degenerative diseases of the pancreas. PA is a polyethiological condition to the formation of which lead chronic (Ammann,1992;Gedam, 2017;Rodríguez, 2020) and acute pancreatitis (Fink, 1988;Rani, 2016;Reuken, 2018), the annual incidence of which ranges from 13 to 45 per 100,000 persons. (Hoilat & Katta, 2021).…”
Section: Introductionmentioning
confidence: 99%